Social development and the Social Summit (a report on Guyana, Jamaica, Trinidad and Tobago) - Thomas, Clive Y. ([s.n.] [S.l.], 1995)
Analyses the social situation in Guyana, Jamaica and Trinidad and Tobago in terms of seven classes of indicators, namely population and geography; the standard-of-living; the social sectors; employment and unemployment; poverty; income distribution; and, looks at the social process at work. Presents recommendations and proposals.